2017
DOI: 10.1016/j.athoracsur.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Continued Successful Evolution of Extended Criteria Donor Lungs for Transplantation

Abstract: Future studies examining lung transplantation outcomes with EVLP must consider the excellent results that can be achieved by using marginal lungs and conventional donor management. It is important to consider that adopting a strategy of perioperative lung donor evaluation and intervention allows use of what are considered marginal lungs to achieve promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 21 publications
0
53
0
3
Order By: Relevance
“…While the constituent studies of this meta-analysis applied varying EVLP protocols and methodologies, it is clear that EVLP provides the ability to expand the pool of available donor lungs by reconditioning and reassessing lungs not considered suitable under standard criteria lung transplant. Using marginal lungs under extended-criteria for standard protocol lung transplant has been reported as doubling utilization rates to around 30-40% (30,31). Using EVLP however, studies in the present analysis reported conversion rates from EVLP evaluated lungs to transplant ranging from 34% to 97% (8,20,21,23,24,26).…”
Section: Discussionmentioning
confidence: 50%
“…While the constituent studies of this meta-analysis applied varying EVLP protocols and methodologies, it is clear that EVLP provides the ability to expand the pool of available donor lungs by reconditioning and reassessing lungs not considered suitable under standard criteria lung transplant. Using marginal lungs under extended-criteria for standard protocol lung transplant has been reported as doubling utilization rates to around 30-40% (30,31). Using EVLP however, studies in the present analysis reported conversion rates from EVLP evaluated lungs to transplant ranging from 34% to 97% (8,20,21,23,24,26).…”
Section: Discussionmentioning
confidence: 50%
“…lung transplantation, uncontrolled donors after circulatory death marginal donors, 10 and donation after circulatory death (DCD). 11 In the last years, the usage of controlled DCD (cDCD) for lung transplantation has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Donor scarcity in western countries has been recognized in the past decades as a major burden in transplantation medicine, leading to a more extensive utilization of extended criteria donor organs. In lung transplantation, upon utilizing extended criteria lungs, careful donor and recipient selection has repeatedly shown to lead to similar outcomes as compared to utilizing standard donor lungs [3,7], lowering the threshold for routine use of nonideal donors. Structural defects such as fibrotic or bullous parenchymal changes in donor lungs remain unacceptable for lung donation.…”
Section: Discussionmentioning
confidence: 99%
“…Extended criteria donor organs have been successfully used for lung transplantation with similar short-and long-term outcome as compared to standard donor organs [3][4][5][6][7]. A majority of organs are classified as extended criteria donor lungs due to older age, impaired oxygenation, trauma, aspiration or drowning [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%